FBM@AAPBS Annual Meeting 2023 - UiTM, Faculty of Business and Management (UiTM, 2023)
AAPBS Annual Meeting 2023: Fostering Digital and Sustainable Transformation in Business Education was held at the National Taiwan University College of Management, Taipei, on November 9-10, 2023. The halls of the National Taiwan University College of Management buzzed with intellectual enthusiasm as the 2023 Annual Meeting of the Association of Asia-Pacific Business Schools (AAPBS) unfolded in Taipei. This year's theme, "Digital and Sustainable Transformation in Business Education," gathered esteemed deans and scholars from the most prestigious educational institutions across the region to deliberate and exchange visionary insights.